Real Earnings Management, Firm Performance, and Corporate Governance Mechanism - Maria Stefani Osesoga; Rosita Suryaningsih; Febryanti Simon (ADI Publisher, 2021)
The purpose of this study is to analyze the impact of real earnings management on firm performance and the impact of corporate governance as an intervening variable in the relationship between real earnings management and firm performance. The object are companies include in Corporate Governance Perception Index during 2015-2019 and listed in Indonesia Stock Exchange (IDX) and analyzed by using path analysis method. Real earnings management has a significant effect on the firm performance. Furthermore, with corporate governance mechanism within the company, real earnings management significantly affect firm performance. This research is meaningful, but has limitations. The result cannot be generalizing because the sample only companies that listed in CGPI and IDX period 2015-2019. The research implication are as follows: top level management should be cautious about credit policy, cash flow from operation, discretionary expenditures, and production. Earnings management is one of variable that the most prevalent in recent studies but the proxy for earnings management in the recent studies used discretionary accrual. In this research, real earnings management is used to indicate earnings management which measured by abnormal cash flow from operation. Thus, it may provide some contribution to the literature.